Obtenção e aplicação de sistemas microemulsionados na recuperação avançada de petróleo - Albuquerque, Heraldo da Silva (2008)
Due to the need of increasing production in reservoirs that are going through production decline, methods of advanced recovery have frequently been used in the last years, as the use of conventional methods has not been successful in solving the problem of oil drifting. In this work, the efficiency of different microemulsionated systems in the flow of oil from cores from Assu and Botucatu formations. Regarding drifting tests, cores were calcinated at a temperature of 1000°C, for 18 hours, with the aim of eliminating any organic compound present in it, increasing the resultant permeability. Following, the cores were isolated with resin, resulting in test specimens with the following dimensions: 3.8 cm of diameter and 8.7 cm of length. Cores were saturated with brine, composed of aqueous 2 wt % KCl, and oil from Guamaré treatment station (Petrobras/RN). A pressure of 20 psi was used in all tests. After core saturation, brine was injected again, followed by oil at constant flow rate. The system S3 - surfactant (anionic surfactant of short chain), isoamillic alcohol, pine oil, and water - presented the best drift efficiency, 81.18%, while the system S1E commercial surfactant, ethyl alcohol, pine oil, and distilled water presented low drift efficiency, 44,68%